2005
DOI: 10.1002/cncr.21207
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose‐rate brachytherapy as part of a multidisciplinary treatment of nasopharyngeal lymphoepithelioma in childhood

Abstract: Neuropeptide‐containing hippocampal interneurons and dentate granule cell inhibition were investigated at different periods following electrical stimulation‐induced, self‐sustaining status epilepticus (SE) in rats. Immunohistochemistry for somatostatin (SOM), neuropeptide Y (NPY), parvalbumin (PV), cholecystokinin (CCK), and Fluoro‐Jade B was performed on sections from hippocampus contralateral to the stimulated side and studied by confocal laser scanning microscopy. Compared to paired age‐matched control anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 110 publications
1
7
0
Order By: Relevance
“…Between the subjects grouped in this review, the large majority (83.1 %) presented with a Type III tumor. Patients affected by juvenile NPC typically present advanced locoregional disease at diagnosis, with distant metastasis [12], and the American Joint Committee for Cancer Staging system [13] is normally used in the staging of NPC. Our data strongly confirmed this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Between the subjects grouped in this review, the large majority (83.1 %) presented with a Type III tumor. Patients affected by juvenile NPC typically present advanced locoregional disease at diagnosis, with distant metastasis [12], and the American Joint Committee for Cancer Staging system [13] is normally used in the staging of NPC. Our data strongly confirmed this concept.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Other studies [31][32][33][34][35][36] have also shown no noticeable complications and similar rates of long-term local control after intraoperative high-dose-rate radiotherapy (table 2).…”
Section: Disease-specific Outcomesmentioning
confidence: 69%
“…In the study by Nakamura and colleagues, 34 15 children with stage IV nasopharyngeal lymphoepithelioma and one with stage III nasopharyngeal lymphoepithelioma were given high-dose-rate brachytherapy between May, 1992, and May, 2000. Children received two sessions of high-dose-rate brachytherapy (5 Gy) 1 week apart prescribed at 10 mm from the applicators.…”
Section: Disease-specific Outcomesmentioning
confidence: 99%
“…In a similar manner, other authors report using brachytherapy to escalate the high-risk target volume. 18 This approach stands in contrast to the Children's Cancer and Leukaemia Group (CCLG) rare tumor guidelines for managing NPC in pediatric and adolescent patients. These guidelines, based largely on the Manchester, UK experience from 2007, suggest that the necessary dose to the high-risk region is only 45 Gy.…”
Section: Discussionmentioning
confidence: 97%